PEMBELAJARAN PAI DENGAN MODEL PROJECT BASED LEARNING BERBASIS LITERASI DI MTSN 4 JOMBANG - Himmatur Rofi'ah; Haris Supratno (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to: (1) describe the application of PAI learning with a Literacy-based Project Based Learning Model at MTsN 4 Jombang; and (2) describing PAI learning with a Literacy-based Project Based Learning Model that can improve 4C at MTsN 4 Jombang. The type of research used is phenomenological research with a qualitative data approach. The presence of the researcher acts as the main instrument in this research. The data collection technique used is through participatory observation methods, in-depth interviews, and documentation. Data analysis techniques used in this research are data presentation, data reduction, and drawing conclusions. The data validity technique is through source triangulation, method triangulation, and time triangulation. The results of the study show that: (1) the application of PAI learning with the Project Based Learning Model Literacy-Based case studies on students of class VIII L and VIII I at MTsN 4 Jombang, namely, the learning tools that must be prepared by the teacher before teaching are syllabus, lesson plans and worksheets. Literacy-based Students (LKPD) which contains 12 literature on social media. The teacher makes RPP in accordance with the 2013 curriculum and the guidelines in the Circular Letter of the Minister of Education and Culture No. 14 of 2019, the teacher has implemented the steps of the literacy-based Project Based Learning learning model quite well and its application is in the form of RPP and LKPD; and (2) PAI learning with the Literacy-Based Project Based Learning Model can improve Critical Thinking, Creativity, Communication, Collaboration (4C) by applying the 6-step Project Based Learning model which in the process of learning activities has implemented 4C skills which can improve students' skills in critical, creative, communicative and collaborative thinking.